Personality and psychopathology building a clinical science ; selected papers - Millon, Theodore 1929- (A Wiley-Interscience publication, 1996)
In Personality and Psychopathology, Millon provides the reader with a coordinated series of papers that illustrate his unprecedented model for building a unified science of personology and psychopathology. In this effort, he seeks to integrate previously disparate components into a clinical science. Rather than developing independently and being left to stand as largely unconnected functions, Millon argues that a truly mature clinical science will embody explicit: 1) theories, that is, explanatory and heuristic conceptual schemes that enable the development of a formal 2) nosology, a taxonomic classification of disorders that is devised logically from the theory and which permits the development of coordinated 3) instruments, tools that are empirically grounded and sufficiently sensitive quantitatively to enable the theory's hypothesis to be adequately investigated, and from which target areas can be specified for 4) interventions, strategies and tactics of therapy designed in accord with the theory.